THE CAMBRIAN EVOLUTIONARY STAGES OF AGNOSTIDS - Naimark E.B.; Markov A.V. (My University, 2001)
The duration of the existence and geographic ranges of agnostid genera with different morphological characters are analyzed. Genera with no transglabellar furrows and/or transaxial furrows and/or smoothed axial glabellar furrow tend to have smaller geographic and stratigraphic ranges, whereas genera with two transaxial furrows on the cephalon and pygidium and/or long axis are characterized by increased ranges. The Cambrian evolution of agnostids comprises two stages differing in rates of origination and extinction, mean duration, and dominant morphology of the genera. Phases of growth, acme, and decline are distinguished within each stage.
Keywords: Cambrian; Agnostids; Paleozoic::Cambrian; Палеозой::Кембрийская